Report on outcomes and get everyone involved: The Participatory Performance Story Reporting Technique - and Dart, J. (2008)
This paper outlines the background and philosophy of Collaborative Outcomes Reporting (COR) and Performance Story Reporting (PSR), providing an overview of these emerging techniques and showing how they can be used as a framework for reporting on contribution to long-term outcomes (or targets) using mixed methods and participatory process. The report serves as an introduction to these approaches in evaluation and discusses their bias, limitations and where they might best be applied.